Adverse effects of benzodiazepines in psychiatric outpatients - Arbanas, Goran (Array, 2009)
Benzodiazepines are among the most frequently prescribed drugs. Of all their side effects, hip fractures and possibility of developing dependence are usually studied.The aim of this study was to determine how often do psychiatric outpatients suffer from adverse effects of benzodiazepines, and which adverse effects do they notice. 109 patients on two consecutive days were asked to fill in the questionnaire. Among them were 29 women and 80 men. Ten women (1/3) and 20 men (1/4) refused to participate in the study. 68% of women and 93% of men used benzodiazepines at least once in a lifetime; 40% of women used benzodiazepines in the last seven days, and 93% of men (32% of women and 44% of men used benzodiazepines every day for the last seven days)